2SPD-004 Analysis of piperacillin/tazobactam use during its worldwide shortage - Fumero, R García (Eur J Hosp Pharm, 2018)
BACKGROUND: Mid-year supply problems of piperacillin/tazobactam (PT) led the Spanish Agency for Medicines and Health Products (AEMPS) to define a proposal to manage the approaching situation. AEMPS proffered some guidelines depending on the type of infection addressed and the priority of use according to the case. PURPOSE: To analyse patients under PT treatment focusing on drug indication and infection features. To evaluate the prescription adequacy and treatment duration. MATERIAL AND METHODS: Retrospective observational study (June and July 2017), including all patients who received PT, was conducted. The study variables were: demographics, clinical services, initial severity (no sepsis, sepsis or septic shock), origin of infection and acquisition (community- or healthcare-related), therapy type (empiric or targeted), treatment duration, evaluation on day 0 and global evaluation (adequate, not recommended, inadequate or unnecessary). The variables were obtained from the medical records. The results are expressed as frequency measurements (%). RESULTS: Twenty-two patients were included: 40.9% were male and 59.1% were female. Age distribution was: 18.2%<60 years’ old, 50% 60–80 years’ old and 31.8%>80 years’ old. Internal medicine was the main prescribing service (59. 1%). No sepsis was observed in 40.9% of patients, sepsis in 36.4% and septic shock in 13.6%. Origin of infection distribution was: 27.3% skin and soft tissue, 18.2% intra-abdominal and 13.6% urinary tract. Most of the infections were community-related (59.1%). Therapy was basically targeted (63.6%) and lasted a median of 9 days. Therapy evaluation at day 0 versus global evaluation showed: 19 vs 12 adequate, 2 vs 4 not recommended, 0 vs 3 inadequate and 1 vs 2 unnecessary. CONCLUSION: In accordance with AEMPS’ proposal and clinical guidelines, almost every treatment (86.4%) was initially adequate, meaning acceptable antibiotic indication. Global evaluation, in contrast, showed that 36.8% of that proportion of patients was not adequate at the end of treatment, revealing prescribing faults that may be solved by considering treatment duration and de-escalation, especially when there is no other way to address shortage situations. No conflict of interest